Analysis of the Effect of Geopolitical Risks on Economic Resilience in Iran - Mohammed kadhim, Roa'a; Ghobadi, Sara; Shnawa Majeed Al-Zerkani, Hussein; Sharifi Renani, Hossein (Business, Marketing, and Finance Open, 2025)
Economic resilience, defined as the capacity to withstand existing economic and political adversities and crises, affects the lives and choices of individuals in society. Geopolitical risks, arising from war, terrorist attacks, and international disputes, which lead to disruptions in the normal course of international and regional policies, also influence the resilience of the population. The present article aimed to analyze the effect of geopolitical risks on economic resilience in Iran during the period from 2002 to 2023. To this end, the nonlinear ARDL approach was employed, with a focus on decomposing geopolitical risk shocks. The results indicated that, in the short term, positive shocks to geopolitical risks had no effect on economic resilience, while negative shocks exerted a negative effect. In contrast, in the long term, positive shocks to geopolitical risks had a positive effect, and negative shocks had a negative effect on the aforementioned index. The results of the Wald test indicated the asymmetry of geopolitical risks across all time periods. Moreover, long-term oil demand had a positive effect on economic resilience. On the other hand, the findings showed that inflation had no impact on economic resilience in the short term, but had a negative effect in the long term.